Pengaruh Working Capital Turnover, Total Asset Turnover, Asset Growth Dan Sales Growth Terhadap Kinerja Keuangan Perusahaan Consumer Goods Yang Terdaftar Di Bursa Efek Indonesia Selama Tahun 2013-2016 - Shelly Andelline dan Indra Widjaja (Universitas Tarumanagara, 2019)
The purpose of this research is to determine the influence of working capital turnover, total asset turnover, asset growth and sales growth partially and simultaneously to the financial performance of consumer goods companies listed on the Indonesia Stock Exchange during the year 2013-2016. The populations in this research are all manufacturing companies of consumer goods industry listed in Indonesia Stock Exchange. Sampling was done by purposive sampling method. Based on the type of data and analysis, this research is quantitative research and the data source used is secondary data. Data collection method used is direct observation method. Based on multiple linear regression test, it can be concluded that working capital turnover, total asset turnover influence to financial performance while asset growth and sales growth have no influence to financial performance. Simultaneously, the four independent variables significantly influence the financial performance. Based on the coefficient of determination can be concluded that the four independent variables affect the financial performance by 92.65%.